2018
DOI: 10.1002/cam4.1379
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and terminal skeletal muscle differentiation in WT1‐mutant Wilms tumors

Abstract: Wilms tumors (WT) with WT1 mutations do not respond well to preoperative chemotherapy by volume reduction, suggesting resistance to chemotherapy. The histologic pattern of this tumor subtype indicates an intrinsic mesenchymal differentiation potential. Currently, it is unknown whether cytotoxic treatments can induce a terminal differentiation state as a direct comparison of untreated and chemotherapy‐treated tumor samples has not been reported so far. We conducted gene expression profiling of 11 chemotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Tumor volume after pre-operative chemotherapy also predicted tumor recurrence in local blastemal-type WT [83]. Tumors with WT1 mutations do not show volume reduction after chemotherapy, which is thought to be due to chemotherapy-induced skeletal muscle cell differentiation rather than apoptotic cell death [90,91]. However, as we will discuss in more detail in Section 7, germline and somatic WT1 mutations are not independently associated with an increased risk of tumor recurrence.…”
Section: Tumor Volumementioning
confidence: 93%
“…Tumor volume after pre-operative chemotherapy also predicted tumor recurrence in local blastemal-type WT [83]. Tumors with WT1 mutations do not show volume reduction after chemotherapy, which is thought to be due to chemotherapy-induced skeletal muscle cell differentiation rather than apoptotic cell death [90,91]. However, as we will discuss in more detail in Section 7, germline and somatic WT1 mutations are not independently associated with an increased risk of tumor recurrence.…”
Section: Tumor Volumementioning
confidence: 93%
“…32 Moreover, previous research has shown that RELN expression is dramatically elevated in Wilms' tumor and encodes the secreted extracellular matrix protein to modulate cell interactions and migration. 33 Mechanistically, the depletion of RELN functions to impede the aggressive actions of non-Hodgkin lymphoma cells and induces G0/G1 phase arrest and apoptosis. 34 The overexpression of RELN has also been detected in prostate cancer; miR-381-mediated RELN inhibition is capable of enhancing cell apoptosis and autophagy by inactivating the PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Due to hypomethylation in the promoter region, the expression of RELN is elevated in multiple myeloma 32 . Moreover, previous research has shown that RELN expression is dramatically elevated in Wilms' tumor and encodes the secreted extracellular matrix protein to modulate cell interactions and migration 33 . Mechanistically, the depletion of RELN functions to impede the aggressive actions of non‐Hodgkin lymphoma cells and induces G0/G1 phase arrest and apoptosis 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A prescrição da medicação de suporte, também é fundamental para evitar tais efeitos adversos. Isso demonstra que a análise dos exames laboratoriais permite a detecção inicial dos problemas de toxicidade induzida pela quimioterapia, possibilitando o ajuste de dose antes do agravamento da toxicidade, que poderia levar a interrupção do tratamento (BROK et al, 2017;ROYER-PAKORA, 2018;YING et al, 2019;SPREAFICO, 2016). As principais recomendações encontram-se descritas na Figura 2.…”
Section: Estudo Observacionalunclassified